2017
DOI: 10.1007/s11738-017-2466-x
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of anti- and prooxidants on rhizogenesis from hypocotyls of Mesembryanthemum crystallinum L. cultured in vitro

Abstract: The enrichment with antioxidants (glutathione or ascorbate) or prooxidants (alloxan, methylviologen, hydrogen peroxide) of root inducing medium significantly decreased rhizogenesis frequency (alloxan, hydrogen peroxide) or inhibited roots regeneration (ascorbate, methylviologen) during the in vitro culture of Mesembryanthemum crystallinum L. hypocotyls. The adventitious roots morphology, root hairs length and density, was also influenced. Changes in the rhizogenesis course were related to the differences in hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The research by Libik-Konieczny et al [59] on rhizogenesis showed the importance of redox balance system for this process, which could be mediated by preventing the negative effects of possible oxidative stress. Isoforms of superoxide dismutase (SOD) and peroxidase (POD) can play a significant role in regulating the content of hydrogen peroxide in the formation of root primordia, as well as in the process of root growth and development [59,60]. The accumulation of ROS in meristematic cells of root tips subjected to stress serves as a signal for autophagy [61].…”
Section: Discussionmentioning
confidence: 99%
“…The research by Libik-Konieczny et al [59] on rhizogenesis showed the importance of redox balance system for this process, which could be mediated by preventing the negative effects of possible oxidative stress. Isoforms of superoxide dismutase (SOD) and peroxidase (POD) can play a significant role in regulating the content of hydrogen peroxide in the formation of root primordia, as well as in the process of root growth and development [59,60]. The accumulation of ROS in meristematic cells of root tips subjected to stress serves as a signal for autophagy [61].…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Mesembryanthemum crystallinum (collected at the Guadiamar riverbed) and commercial seeds of Medicago sativa (alfalfa) cv. Aragon were surface disinfected by immersing them in 70% ( v / v ) ethanol for 2 min, followed by immersion in commercial bleach solution (1:2, v / v ) for 10 min, before they were finally washed three times with sterile, distilled water [ 90 ]. Seeds were pregerminated in water agar (9 g∙L −1 ) for 48 h at 25 °C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds of M. crystallinum (three batches of one hundred seeds each) were surface disinfected by treatment with 70% ethanol (2 min), washing with sterile distilled water, followed by treatment with 2.5% sodium hypochlorite (10 min) with gentle shaking, and finally exhaustive washing with sterile distilled water [78]. Once sterilized, they were deposited on moist sterile perlite in Petri dishes (25 seeds per plate).…”
Section: Effect Of Inoculation On Seed Germinationmentioning
confidence: 99%